Automatic 2D Segmentation of an Intracardiac Catheter Basedon MSER Blob Detector and Eccentricity; Advances in Intelligent Systems Research; Vol. 158 : Critical Infrastructures: Contingency Management, Intelligent, Agent-based, Cloud Computing and Cyber Security (IWCI 2018) - Danilov V. V. Vyacheslav Vladimirovich; Skirnevsky I. P. Igor Petrovich; Gerget O. M. Olga Mikhailovna; Manakov R. Roman (2018, 2018)
Title screen